2012
DOI: 10.1016/j.jdiacomp.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Is silent myocardial infarction more common in women with type 2 diabetes than in men?

Abstract: Objective Our aim was to determine if silent myocardial infarction (MI) is more common in women with type 2 diabetes than in men. Our secondary aim was to examine the relationships between silent MI and risk factors for cardiovascular disease. Research Design and Methods The Action to Control Cardiovascular Risk in Diabetes (ACCORD) database was used to determine if women had more silent MI on baseline electrocardiograms (ECGs) than did men with a similar unremarkable cardiovascular history. MI was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
5
0
5
Order By: Relevance
“…[13] Our patient did not have any feature of or predisposing factor for autonomic neuropathy. It has been reported that normal patients perioperatively have higher incidence of silent myocardial ischemia.…”
Section: Discussionmentioning
confidence: 97%
“…[13] Our patient did not have any feature of or predisposing factor for autonomic neuropathy. It has been reported that normal patients perioperatively have higher incidence of silent myocardial ischemia.…”
Section: Discussionmentioning
confidence: 97%
“…In the diabetic population, a greater prevalence of silent MI has been observed in women in the Fremantle [64], and in the UKPDS [33] studies. In the ACCORD cohort no evidence was found that silent MI, as detected by the Minnesota code, was more common in women than in men; rather, women showed a higher heart disease mortality rate compared to men [86]. Usually women complain less of chest pain and of typical symptoms of acute coronary syndrome, especially diabetic women [87,88], but often asymptomatic women have a worse prognosis than asymptomatic males [86,89].…”
Section: Factors Associated With Silent Coronary Artery Disease In Tymentioning
confidence: 97%
“…Durante todo o acompanhamento, 5% dos indivíduos com NP apresentaram eventos cardiovasculares em comparação com 2,8% de indivíduos sem NP (13) . Pacientes com doença aterosclerótica portadores de DM têm sido sujeitos de diversas pesquisas com o intuito de avaliar a melhor forma de estratificação de risco, com o objetivo de reduzir as complicações na fase aguda (8)(9)(10)(11)(12)(14)(15)(16)(17)(18) . Diante da dificuldade na triagem nos serviços de emergências em pacientes DM, em decorrência da presença de sinais atípicos secundários à neuropatia periférica, são altamente indicados instrumentos que possam facilitar a identificação destas condições ou mesmo estratificar o risco de mortalidade/ complicações destes pacientes.…”
Section: Neuropatía Periférica Y Signos Clínicos De Síndrome Coronariunclassified